Teoria e práxis: Oliveira Vianna como consultor jurídico do Ministério do Trabalho, Indústria e Comércio (1932-1940) - Fontana, Felipe (Universidade Federal de São Carlos, 2017)
In this work we will present some considerations about the work developed by Oliveira Vianna in the instances of the Brazilian State between 1932 and 1940. The author, known for being an interpreter of Brazil and a sharp analyst of national political institutions, played an important role as a statemaker, especially in the orientation of labor laws in the golden period of consolidation of the first regulatory structures of this political-institutional field. As legal adviser, Oliveira Vianna wrote legal reports and technical opinions that were sent to the Ministry of Labor, Industry and Commerce or to other institutions through your link with this institution. This material, assimilated or not in the legislation of the period, is attached to a significant part of the collection of the Casa de Oliveira Vianna Museum, deserving, therefore, a detailed analysis, as an autonomous thematic object. Based on the reading, classification and examination of this set of texts, we are interested in evaluating, above all, the nexus between the author's thought and the content of these materials elaborated during the First Vargas Government. Questions such as the interpretation of Brazilian social formation, culture and ethos, institutions, functions of the State, limitations of liberal individualism, among others, influence in what way the project to regulate the tensions inherent to work? In this direction the proposal is to verify the links, continuities or ruptures between the intellectual of social matrix and the expert consultant of the right, highlighting the expressive context where this relation takes place: the transformations post Revolution of 1930. From another angle, it is intended to analyze the influences that the perspective of immediate practical application of the proposals indicated to the Ministry may have reverberated in the perception and subsequent production of the author. Thus, using a broad set of materials we will investigate two central questions: the presence of Oliveira Vianna's theses in the documents produced by him and, in another hand, the possible effects of the requirements applied to the right, in the field of labor, to the intellectual production of the author. In general, we believe that there are pertinent links between the author's thought and his trajectory as a statemaker (either in transposing an intellectual thesis to the applied field or in verifying how the context and objectives of theoretical-practical work influenced conceptions and the later analyzes of the intellectual). Added to this and also as an important result of this work we find, in a less latent way, the existence of some contradictions, discrepancies or dissociations between what Oliveira Vianna ratified in his works (in his theory and work) and what he suggested as a statemaker and legal adviser to the Ministry of Labor, Industry and Commerce (in the documents produced by him). Finally, it is worth mention that emerge as a subsequent result of our research the presentation, analysis and specification of the technical-legal work of Vianna between the years of 1932 and 1940 emerges (a matter that, moreover, is a gap in the studies concerned with the author's thinking, his intellectual production and his professional trajectory as interpreter of Brazil).
Theory and practice: Oliveira Vianna as consultant of the Ministry of Labor, Industry and Commerce (1932-1940)
Keywords: Oliveira Vianna; Intelectuais e Statemakers no Brasil; Primeiro Governo Vargas; Ministério do Trabalho, Indústria e Comércio; Pensamento Vianniano; Oliveira Vianna; Intellectuals and Statemakers in Brazil; First Vargas Government; Ministry of Labor; Industry and Commerce; Oliveira Vianna’s Thought; CIENCIAS HUMANAS::CIENCIA POLITICA::TEORIA POLITICA